(untitled) (Journal of Medical & Health Sciences Review, 2025)
Preoperative: Spinal anesthesia is the preferred technique for all elective operations below umblical region, including caesarian sections, because it leads to minimal handling of the airway And hence decreases the incidence of hypoxemia and aspiration. However spinal activation of sympathetic supply can lead to hypotensive effects and, as a result, negative consequences on both maternal and fetal health. To reduce detrimental peripheral vasodilation effects, prophylactic vasopressors are prescribed, especially phenylephrine acting on the α-adrenergic receptor subtype. The purpose of this study was to compare the prophylactic effect of phenylephrine versus placebo on hypotension in parturients who were to undergo cesarean section under subarachnoid block. Methods: Sixty full-term participants in ASA Class I and II, who were selected for elective cesarean sections were included in the study and further randomized into two groups. The group A patients who were assigned to solution one received 0.5 ml of phenylephrine intravenously before spinal anesthesia, and the group B patients who were assigned to solution two received 0.5 ml of normal saline. Spinal anesthesia was done at L3-L4 intervertebral space with 0.5% hyperbaric bupivacaine. Consent was obtained from all the participants before the study, and they had their systolic mean and diastolic blood pressure measured before spinal injection and at 5, 10, 15 and 30 minutes. Hypotension was established as a fall of blood pressure below baseline values by 20% or more. Statistical evaluation was done using software Statistical Product and Service Solution (SPSS) version 25 with a test of significance at p<0.05. Effects: Prophylactic phenylephrine reduced the incidence of hypotension as compared to placebo. In Group A, the incidence was 26.0% compared to 63.1% in Group B. Considering the tendency of change in blood pressure values and a detailed secondary analysis, the effectiveness of phenylephrine in terms of hemodynamic monitoring was proved. Conclusion: From the evidence presented in the paper, one may conclude that prophylactic use of phenylephrine positively influences maternal and neonatal outcomes by preventing spinal-induced hypotension during cesarean sections. It is therefore advisable that more elaborate multicentric trials be carried out to support these observations. [1–5]